Private equity : history, governance, and operations - Cendrowski, Harry (Hoboken, N.J. : Wiley, 2012)
'An authoritative guide to understanding the world of private equity (PE) investing, governance structures, and operational assessments of PE portfolio companiesAn essential text for any business/finance professional's library, Private Equity: History, Governance, and Operations, Second Edition begins by presenting historical information regarding the asset class. This information includes historical fundraising and investment levels, returns, correlation of returns to public market indices, and harvest trends. The text subsequently analyzes PE fund and portfolio company governance structures. It also presents ways to improve existing governance structures of these entities. A specific focus on portfolio company operations, including due diligence assessments, concludes the text. Seamlessly blends historical information with practical guidance based on risk management and fundamental accounting techniques Assists the book's professional audience in maximizing returns of their PE investments Highly conducive to advanced, graduate-level classroom use Purchase of the text includes access to a website of teaching materials for instructional use Learn more about PE history, governance, and operations with the authoritative guidance found in Private Equity: History, Governance, and Operations, Second Edition'--
Includes bibliographical references and index.
Keywords: Private equity